KONSEP DASAR ANALISIS KEBIJAKAN PENDIDIKAN - Supangi, Hendra Mahardika (El-FAKHRU, 2023)
This journal explains how analysis in the world of education and how to implement it by the values ​​that lead to changes in the world of education. Educational policy analysis is a procedure using data to produce information as well as for the formulation of solving an educational problem, and also as an applied social science structured with the aim of the substance of educational policy to make it easier to identify problems in education. Therefore the government and certain parties improve and maintain policies that lead to the common good in education.